Bauran Pemasaran Pada Usaha Rekreasi Pemancingan Nagaya Desa Kotapulu - Rizki Eka Putri Utami; Farid Farid; Anisah Anisah (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
The purpose of serving in the village with the mission of building a rural economy through the potential in the village is the fisheries sector, as well as to broaden business actors' insight into the application of the marketing mix. The potential in Kotapulu Village is in the fisheries sector. Nagaya fishing is one of the businesses as a means of community recreation. The development of inland fisheries in Central Sulawesi Province has quite large potential for freshwater and brackish water fisheries resources, which if managed optimally can provide a sizeable contribution to the region. Technical data collection is carried out through counseling, interviews and documentation that can answer existing problems. , and so on the data were analyzed descriptively qualitatively. From the results of this study, the Marketing Mix) or 7 P which consists of: Product, Price, Place, Promotion, Process, Physical Environment used in the Nagaya fishing recreational business is in accordance with the existing procedures, while for application in the field there are several obstacles that arise in terms of Promotion, so that the Marketing Mix is not going well.